2017
DOI: 10.1038/s41598-017-03921-4
|View full text |Cite
|
Sign up to set email alerts
|

Hif-1α Knockdown Reduces Glycolytic Metabolism and Induces Cell Death of Human Synovial Fibroblasts Under Normoxic Conditions

Abstract: Increased glycolysis and HIF-1α activity are characteristics of cells under hypoxic or inflammatory conditions. Besides, in normal O2 environments, elevated rates of glycolysis support critical cellular mechanisms such as cell survival. The purpose of this study was to analyze the contribution of HIF-1α to the energy metabolism and survival of human synovial fibroblasts (SF) under normoxic conditions. HIF-1α was silenced using lentiviral vectors or small-interfering RNA (siRNA) duplexes. Expression analysis by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 48 publications
3
37
0
Order By: Relevance
“…At least three different experiments were performed and data were expressed as mean ± SD. *p < 0.05 [54], which provides strong evidence that HIF-1α plays an important role in cell proliferation and survival processes. Moreover, some studies have pointed to the importance of aerobic glycolysis in normal proliferating cells as a mechanism for minimizing oxidative stress [55], considering that pyruvate, generated by glycolytic metabolism, may be an efficient scavenger of ROS and therefore protect cells from oxidative stress [56].…”
Section: Discussionmentioning
confidence: 71%
“…At least three different experiments were performed and data were expressed as mean ± SD. *p < 0.05 [54], which provides strong evidence that HIF-1α plays an important role in cell proliferation and survival processes. Moreover, some studies have pointed to the importance of aerobic glycolysis in normal proliferating cells as a mechanism for minimizing oxidative stress [55], considering that pyruvate, generated by glycolytic metabolism, may be an efficient scavenger of ROS and therefore protect cells from oxidative stress [56].…”
Section: Discussionmentioning
confidence: 71%
“…HIF-1α is the focus of the majority of studies due to its expression in all cells of all metazoan species and it transcriptionally regulates multiple genes that mediate glycolysis ( 24 ). HIF-1α activity is mainly regulated post-transcriptionally in response to hypoxia; consequently, HIF-1α serves a critical role in regulating glycolysis through its downstream target gene GAPDH under hypoxic conditions ( 25 ). In the present study, hypoxia was demonstrated to upregulate the expression of HIF-1α, and therefore partially promote glycolysis in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…This allows heterodimerization of HIF1α with its β-subunit, and translocation into the nucleus where HIF1α binds to hypoxia-response elements linked with a variety of genes involved in various cellular processes, including inducing pfkfb3 and IL1 β transcription ( 168 , 169 ). Moreover, GLUT1, as well as a number of other glycolytic enzymes such as phosphofructokinase, are upregulated to promote anaerobic glycolysis, to compensate for the lack of OXPHOS ( 170 172 ). Iron chelator-induced inhibition of PHD proteins and the resulting HIF1α stabilization encompasses the potential to trigger this molecular cascade during Mtb infection under aerobic conditions, thus, boosting the pro-inflammatory response of the infected host macrophage and promoting clearance of the infection.…”
Section: Fine-tuning Hif1α and Iron; A Mechanism To Support Innate Homentioning
confidence: 99%